Challenges and Opportunities in the Field Of Information and Communications Technology (Ict) due to Covid-19 Pandemic and Migration Towards The New Normal - Ravenal A. De Jesus , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper presented events and scenarios involving the roles of engineering and technology. This paper also covered various industry settings where challenges and opportunities in the field of Information and Communication Technology (ICT) are prevalent and significant. First, summary of historical events involving pandemic and/or plague was introduced. The term quarantine was emphasized in this paper as this involves movement control that could hamper the economy. Such movement controls are called in various names depending on the degree of strictness enforced by respective countries (lock – down, community quarantine, zoning containment and so forth). Second, stages and impacts of different Industrial Revolutions were discussed. Although digital transformation was associated only during the Third Industrial Revolution, it led to numerous technological advancements. Drawbacks of technological advancements were also discussed specifically the right sizing of numerous companies and organizations. Third, selected technologies were showcased. These include the following but not limited to: Public Key Infrastructure (PKI), Rural Impact Sourcing (RIS) and Disaster Risk Reduction Management (DRRM). While these technologies were tailor-fit for Philippine scenarios, faithful reconstruction is possible in order to be tailor-fit in other countries both affected and unaffected by COVID-19 Pandemic. Fourth, provisions for agenda of Gender and Development (GAD) are also presented pursuant the thrusts of international mandates to empower different sectors of the society. Specifically, ICT based and ICT enabled jobs give equal opportunities. Fifth, ICT challenges and opportunities stipulated in this paper were evaluated from local to global perspective towards resilient and sustainable economy.